2009
DOI: 10.1017/s0266462309990328
|View full text |Cite
|
Sign up to set email alerts
|

Developing medical device technologies from users' perspectives: A theoretical framework for involving users in the development process

Abstract: Objectives: To suggest an acceptable and generic theoretical framework for involving various types of users in the medical device technology (MDT) development process (MDTDP). Methods:The authors propose a theoretical framework suggesting different routes, methods and stages through which various types of medical device users can be involved in the MDTDP. Results:The suggested framework comprises two streams of users' involvement in MDT development i.e. what might be called the end users' stream and the profes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
146
0
22

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(177 citation statements)
references
References 36 publications
0
146
0
22
Order By: Relevance
“…This research builds on a number of frameworks which have been developed over the last 15 years to guide the design of AT. Shah and Robinson [32] formulated a theoretical framework for the development of medical and assistive technologies. They concluded that two streams of user involvement are necessary to facilitate the participation of both end-users and professional users.…”
Section: Introductionmentioning
confidence: 99%
“…This research builds on a number of frameworks which have been developed over the last 15 years to guide the design of AT. Shah and Robinson [32] formulated a theoretical framework for the development of medical and assistive technologies. They concluded that two streams of user involvement are necessary to facilitate the participation of both end-users and professional users.…”
Section: Introductionmentioning
confidence: 99%
“…This strategy was based on several existing models for the design of medical devices ( Figure 2). [10][11][12] From November 2010 to September 2012 we conducted three substudies: (A) a user requirements study, (B) a usability test of the system in a laboratory situation and (C) a pilot study in two practices.…”
Section: Methodsmentioning
confidence: 99%
“…Especially, the involvement of the end users produces good results in assailable evaluation tasks like tested before [5,[21][22][23]. In this group, think-aloud analysis and questionnaires are suitable methods.…”
Section: Selection Of Evaluation Methodsmentioning
confidence: 99%